2014
DOI: 10.1186/2049-9957-3-16
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of, attitudes towards, and practice relating to schistosomiasis in two subtypes of a mountainous region of the People’s Republic of China

Abstract: BackgroundSchistosomiasis japonica is still endemic in the People’s Republic of China (P.R. China) in five provinces of lake and marshland regions and in two provinces of mountainous regions. Studies elucidated that individual and community perception, attitudes towards schistosomiasis, and hygiene behaviors were crucial factors for preventing schistosomiasis. This study sought to assess the knowledge of, attitudes towards, and practices (KAP) relating to schistosomiasis in two subtypes of a mountainous region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…Most of the residents and BHWs knew that Schistosoma infection can be acquired while farming in infected rice fields, engaged in fishing, or in contact with infected freshwater. However, becoming infected with Schistosoma through contact with infected water was not a very common response in surveys conducted in China and Swaziland (Maseko et al, 2016;Liu et al, 2014). Similar to the present study findings, the misconception that the infection can be acquired by the consumption of contaminated water or food was also found to be a common response in African surveys (Acka et al, 2010;Odhiambo et al, 2016;Mwanga et al, 2004;Maseko et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Most of the residents and BHWs knew that Schistosoma infection can be acquired while farming in infected rice fields, engaged in fishing, or in contact with infected freshwater. However, becoming infected with Schistosoma through contact with infected water was not a very common response in surveys conducted in China and Swaziland (Maseko et al, 2016;Liu et al, 2014). Similar to the present study findings, the misconception that the infection can be acquired by the consumption of contaminated water or food was also found to be a common response in African surveys (Acka et al, 2010;Odhiambo et al, 2016;Mwanga et al, 2004;Maseko et al, 2016).…”
Section: Discussionsupporting
confidence: 81%
“…Education plays an important role in people’s perceptions and practices of controlling schistosomiasis [ 35 ]. Previous studies from Africa and Asia showed that the odds of having a lower knowledge about schistosomiasis were significantly higher in the respondents who had a primary education level or below [ 36 , 37 ]. In agreement with these findings, our study showed a significant impact for the level of education on the population’s KAP concerning schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…[ 46 ] raised some issues pertinent to snail control, such as a decline in snail related funding and a concomitant decline, to a shockingly low level, as well as the availability of investigators and young workers who are able to identify medically relevant snails. Great success has been achieved in many countries, such as China and Egypt, in reducing the transmission, prevalence and morbidity of schistosomiasis [ 36 , 52 , 53 ]. The MDA-based strategy was fundamental in this success hand-in-hand with health education campaigns and capacity building through the training of personnel working in rural health units or involved in reducing the roles of humans and animals as sources of infection for snails [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge of, attitudes towards, and individual responses in light of this, especially by parents and influential community members, are crucial factors for preventing and controlling parasitic diseases. However, people in poor rural areas, especially children, have a low awareness of parasitic diseases [ 85 , 121 ]. Health education packages, aiming to improve knowledge and awareness and change in hygiene behavior, are an effective way to prevent parasitic diseases [ 122 ].…”
Section: Reviewmentioning
confidence: 99%